Micropolar Nanofluid Flow, Thermal and Mass Transfer Properties Across a Stretching Sheet With a Predetermined Surface Heat Flux - Hymavathi, D. (Communications in Mathematics and Applications, 2023)
The features of two-dimensional immiscible laminar flow of micropolar nanofluid over an unstable stretching sheet with a predetermined surface heat flux are examined in this problem. The thermal boundary conditions have an impact on heat transfer properties. The similarity transformations are utilized to transfigure highly non-linear guided PDE into ODEs. Shooting technique is used to resolve these equations. There are several flow characteristics that are relevant to this issue, including the unsteadiness parameter (S), material parameter (m), viscosity (K), Prandtl number (Pr), Brownian motion parameter (Nb), and thermophoretic parameter (Nt). Graphs are used to study the impact of various flow parameters on liquid velocity, micropolar, temperature, and nonoparticle concentration profile. In order to obtain the findings for this problem, we used the tbvp4c Matlab programme. We noticed that velocity profile, thermal profile, microrotation of the particle, and nanoparticle concentration profile all diminish as an unsteady number S increasing, micropolar profile increases. With a rise in boundary parameter m, the micropolar fluid profile and the concentration of nanoparticle profiles are dropping while the velocity profile and temperature profile are rising. The temperature profile is rising while the volume fraction of nanoparticle is falling as the Brownian motion Nb increasing. The thermal profile and nanoparticle concentration profile both rise with an increase in the thermophoretic number Nt. With an increasing of magnetic field parameter M, the velocity profile and micropolar profile are declining, but the thermal and nanoparticle concentration profile is rising.